Measuring loss of access to the land and its impact on place attachment: The case of the historical mining community of Puchoco, Chile - María Isabel López-Meza; Alejandra Brito-Peña (Urbano)
Landscape change is a key variable in place attachment and identity. Moving on from previous studies in the field of landscape and planning research, this paper specifically aims to explore the impact of loss of access to urban green and open space on memories and emotional connections to place. These issues were examined in the context of a former coal mining community with strong social cohesion and local identity in order to analyze the impact of urban transformation on the past and present meanings of place for current inhabitants. Research methods involved a mixture of qualitative tools including focus groups, life narratives, blank mapping research, and cartographic analysis of land use change. Results present powerful evidence of the important detrimental effects that unplanned landscape change can have on everyday access to open spaces, and in consequence, on positive meanings of place. Moreover, these dynamics can deeply affect historical company towns undergoing processes of decay after industrial closure. In this sense, this study can contribute to developing recommendations for current planning practices within the context of heritage management.